2020
DOI: 10.1073/pnas.1919065117
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic dietary shift maintains sequestered toxins in chemically defended snakes

Abstract: Unlike other snakes, most species ofRhabdophispossess glands in their dorsal skin, sometimes limited to the neck, known as nucho-dorsal and nuchal glands, respectively. Those glands contain powerful cardiotonic steroids known as bufadienolides, which can be deployed as a defense against predators. Bufadienolides otherwise occur only in toads (Bufonidae) and some fireflies (Lampyrinae), which are known or believed to synthesize the toxins. The ancestral diet ofRhabdophisconsists of anuran amphibians, and we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…lateralis (Takeuchi et al, 2011(Takeuchi et al, , 2014(Takeuchi et al, , 2018. Finally, we agree with Takeuchi et al (2018) in recovering a derived clade that includes R. nuchalis, R. pentasupralabialis, and R. leonardi, known as the R. nuchalis group (Yoshida et al, 2020). Furthermore, both Takeuchi et al (2018) and we find that R. guangdongensis and R. swinhonis are more closely related to the R. nuchalis group than to other Rhabdophis.…”
Section: Discussionsupporting
confidence: 85%
“…lateralis (Takeuchi et al, 2011(Takeuchi et al, , 2014(Takeuchi et al, , 2018. Finally, we agree with Takeuchi et al (2018) in recovering a derived clade that includes R. nuchalis, R. pentasupralabialis, and R. leonardi, known as the R. nuchalis group (Yoshida et al, 2020). Furthermore, both Takeuchi et al (2018) and we find that R. guangdongensis and R. swinhonis are more closely related to the R. nuchalis group than to other Rhabdophis.…”
Section: Discussionsupporting
confidence: 85%
“…Red rectangles represent beetle specimens that tested positively for lucibufagins, blue rectangles represent beetle individuals that were devoid of these compounds. Further occurrences of bufadienolides are known from Photuris versicolor (Photurinae) [14], Diaphanes lampyroides [17], Ellychnia corrusca [16], Lucidota atra [15], Photinus ignitus, P. marginellus [9,12], and P. pyralis (Lampyrinae) [11,12]. Absence of lucibufagins was further demonstrated for Aquatica lateralis (subfamily Luciolinae) and the click beetle Ingnelater luminosus (Elateridae) [24].…”
Section: Resultsmentioning
confidence: 97%
“…Lucibufagins in fireflies were first described by Eisner et al from the north North-American species Photinus marginellus (LeConte 1852) [9]. In addition, these compounds were found in Photinus ignitus (Fall 1927) [10], Photinus pyralis (Linnaeus 1767) [11,12], Photuris versicolor (Fabricius 1798) [13,14], Lucidota atra (Olivier 1790) [15], and recently Ellychnia corrusca (Linnaeus 1767) [16] and Diaphanes lampyroides (Olivier 1891) [17]. While almost all records of lucibufagins in fireflies were made for North-American species, Tyler et al were the first who reported the occurrence of these compounds in the Eurasian species Lampyris noctiluca (Linnaeus 1767) [18].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to having Duvernoy’s gland to produce venom, some snakes also have another organ, the nuchal gland, to store venomous fluid ( Figure 2 B). The nuchal gland, also named nucho-dorsal gland or cervical gland, is a special defensive system in some species of snakes such as the Rhabdophis genus [ 19 , 20 ]. These snakes consume a poisonous prey and conserve the poison in their nuchal glands to spray the stored poison for defense.…”
Section: Snake Venom/toxin Cause Ocular Complicationsmentioning
confidence: 99%